Comment on Bisson et al. Novel Approach to Proficiency Testing Highlights Key Practice Variations in Cancer Biomarker Delivery. J. Mol. Pathol. 2024, 5, 1–10 - Emina Torlakovic; Nicola Normanno (Journal of Molecular Pathology, 2024)
We have read, with great interest, a recently published article by Bisson KR et al [...]